(3eQGJY GdZRdGf aj hUa GdMSGf ef GdZdeGfs - (3eMeO Hf MSf Hf Ydj Hf YKeGf GdfhGLj GdTGaYj , TeS GdOjf,J (B859 (3g` s ((3eMeO CafOj s)
(3ChdgG (B:s
(3CeG HYO MeO ddg GdPj Ndb GdEfSGf aj CMSf Jbhje abO SCdfj dYV GdENhGf Cf CLeY dg ofHPI aj GdMSGf ef GdZdeGf s
(3BNQgG (B:s
(3bGd dj Ndj JRhL JSJQM ef CPi GdabQ hJSJZfj jbjf gPG BNQ eG GfJgj EdjfG ef GdCTYGQ GdMSGf aj hUa GdZdeGf, hfSCd Gddg GdSeGM s
(3fSNI KGdKIs
(3JJab aj ChdgG eY GdfSNI GdChdi HGNJdGa aj HYV GdCdaGXs
(3HgG fXGe GdJYbjHIs
(3HgG JbOje hJCNjQ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B88 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B203 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B200s
Keywords: (3GdCOHs